Letter (copy) - Citrine, Walter, 1887-1983
012a-0085-001 Secretary's WMC/FEM/KMS/644 3rd June, 1938. Señor Don Pablo de Azcarate y Florez, Spanish Embassy, 24, Belgrave Square, S.W.1. Dear Señor Azcarate, Your letter of the 28th May has been passed on to me by Mr. Elvin and will be read to the next meeting of the National Council of Labour. I know they will appreciate very much the references made to the assistance they were able to give through the Albert Hall meeting. Yours sincerely, General Secretary 292/946/12a/85